Performance of open pore metal foam heat sinks fabricated with thermally sprayed interface. (25th July 2016) - Aly, S.P.; Arif, A.F.M.; Al-Athel, K.S.; Mostaghimi, J.; Zubair, S.M.
Highlights: Performance of metal foam heat sinks fabricated with thermally sprayed interface is evaluated. The performance is compared with conventional solid fin and metal foam glued heat sinks. 45° is the best orientation between the multiple fin heat sinks and the air flow. Several appropriate metrics for performance evaluation of metal foam heat sinks is presented. Abstract: In this paper, the result of an experimental study on thermal performance of different metal foam heat sinks is presented and compared with conventional solid heat sink. Experiments were performed on aluminum metal foams having 93% porosity with pore density of 4 and 8 PPI (i.e. pores per inch). The forced convection results show that heat sink with thermal spray coating outperforms a thermally glued sample with up to 9.8% more temperature drop under same operating test conditions. Air flow speed variations reveal that heat transfer rate changes significantly with the variation of air speed. Further studies with multiple fin samples show that 45° is the best orientation between the heat sink and the flow for maximum heat dissipation. For a single fin, the best orientation is 90°. Results show that power dissipation at a fixed fin base temperature is an appropriate metrics for comparing thermal performance of metal foam heatsinks.